Increasing ideological tolerance in social psychology. (8th September 2015) - Inbar, Yoel; Lammers, Joris
Abstract: We argue that recognizing current ideological diversity in social psychology and promoting tolerance of minority views is just as important as increasing the number of non-liberal researchers. Increasing tolerance will allow individuals in the minority to express dissenting views, which will improve psychological science by reducing bias. We present four recommendations for increasing tolerance.